Juventude, lazer e sociabilidade: trajetos e percursos na noite - Pires, Eliane Nogueira (2004)
This ethnographic paper is concerned with the understanding of youths of Vitória da Conquista, a city located in the Southwest part of the State of Bahia, Brazil, in relation to their night leisure as well as their new forms of night sociability. My objective is to know these youths, the intervals of their daily night life, their spaces and territories and their contact of sociability. In order to contextualize this paper, I intend to study the daily life of a group of youths, age 19 to 24, whose parents are professionals, professors, teachers and small business entrepreneurs. The transgression and excesses of youth will not be taken into consideration in this paper. I try to identify a new form of sociability, group meetings, lave affairs, adventures, pleasures, disagreements, fears, violence, contradictions and other kinds of relevant experiences lived by these youths. The paper had as its base some testimonies given by the informants in the years of 2000 and 2004. The methodology used for this paper was designed to apprehend the dynamics of leisure of this group of city youth that goes out at night looking for freedom, excitement, entertainment and other kinds of night life. The night is seeing as a space in which these youths can reaffirm their experience and condition of being young. It is algo a time when they can live their lives without being watched; therefore they enjoy themselves more, without a lot of commitments with their sociability and affective exchanges. However, some prejudica and hierarchical order were found in this space seeing as a space of freedom. It was algo evident that these youths use this night life as a space of cultural practices and the main visible form of communication and resistance, through which they express their behavior and attitudes, and position themselves in relation to society